Chapter 22 Systemic Governance - Csaba, László (Taylor & Francis, 2023)
This chapter, being halfway between abstract economic theory and policy analysis, addresses one of the most contested issues in comparative economic studies, namely the role of human deliberation versus spontaneity at the macroeconomic level. To arrive at new insights. It adopts a cross-regional perspective and speculates, if the counter-intuitive practices of China, based on pragmatism and experimentation, trial and error, has indeed been superior to social engineering, as practiced in various forms across Europe. It also highlights the limitations to theoretical generalizations, i.e., making claims that remain valid at any time and any place, as mainstream economics suggests of its own insights.